2011
DOI: 10.1007/978-3-642-19448-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Parallelization Schemes for Memory Optimization on the Cell Processor: A Case Study on the Harris Corner Detector

Abstract: Editors : Per Stenström Publisher : Springer Berlin HeidelbergInternational audienceThe Cell processor is a typical example of a heterogeneous multiprocessor on-chip architecture that uses several levels of parallelism to deliver high performance. Reducing the gap between peak performance and effective performance is the challenge for software tool developers and the application developers. Image processing and media applications are typical "main stream" applications. We use the Harris algorithm for the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Accelerated implementation is fundamentally investigated by Wu, Lam and Srikanthan in [6], and by Tadonki et al in [36]. An implementation on the CELL processor is provided and discussed by Saidani et al in [35]. The last two contributions also provide a qualitative and quantitative study of tiling.…”
Section: Related Work On Harris Detector Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerated implementation is fundamentally investigated by Wu, Lam and Srikanthan in [6], and by Tadonki et al in [36]. An implementation on the CELL processor is provided and discussed by Saidani et al in [35]. The last two contributions also provide a qualitative and quantitative study of tiling.…”
Section: Related Work On Harris Detector Implementationmentioning
confidence: 99%
“…The SIMD part is left to the compiler (the native one for each considered architecture), and shared memory parallelism is implemented with OpenMP (through classical directives. Other studies of Harris corner detection and its applications can be found in [35,36,37,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…loads from unaligned memory addresses, so that each value of the neighborhood can be available as a SIMD vector. To limit the number of such loads, a technique called the register rotation technique [16] is often used. This technique allows filter-like algorithms to perform only one load per iteration, swapping neighborhood values as the algorithm goes forward.…”
Section: Sliding Window Iteratormentioning
confidence: 99%
“…Différentes implantations ont été évaluées en détail dans (Saidani et al, 2008), seuls les résultats de la version Halfpipe sont analysés ici. Les SPE du Cell ayant été conçus pour faire du calcul SIMD et non du calcul scalaire, les versions scalaires sont toutes inefficaces, le gain global ×214 n'est donc pas significatif.…”
Section: Le Cellunclassified